2005
DOI: 10.1051/vetres:2005030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood and milk non-specific immune parameters in heifers after calving in relation to udder health

Abstract: -A practical protocol to study udder immune status in field conditions was planned with the aim to assess different non-specific immune parameters in milk samples from dairy heifers during the periparturient period. Five herds located in northern Italy were selected and overall 39 heifers were enrolled in the trial. Milk samples were taken at 7, 14, 21, 28, 45, 60, and 75 days after calving. The parameters assessed were N-acetyl-β-glucosaminidase (NAGase), lysozyme, respiratory burst (RB), somatic cell counts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…This statistical procedure allows to represent the evolution of the proportion of true positive cases (also called sensitivity) as a function of the proportion of false positives cases (corresponding to 1 minus specificity), and to evaluate a binary classifier test to diagnose a disease. In our case disease was defined as a milk sample with >200,000 cells/mL (Piccinini et al 2005;Zecconi et al 2018). Table 2 describes the parameters calculated to evaluate DSCC diagnostic test and the abbreviations used in the text.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This statistical procedure allows to represent the evolution of the proportion of true positive cases (also called sensitivity) as a function of the proportion of false positives cases (corresponding to 1 minus specificity), and to evaluate a binary classifier test to diagnose a disease. In our case disease was defined as a milk sample with >200,000 cells/mL (Piccinini et al 2005;Zecconi et al 2018). Table 2 describes the parameters calculated to evaluate DSCC diagnostic test and the abbreviations used in the text.…”
Section: Discussionmentioning
confidence: 99%
“…However, the progressive decrease of mean SCC in dairy herds worldwide is further affecting in SCC accuracy as a subclinical mastitis marker. Currently, a level of 200,000 cells/mL is considered the threshold to identify subclinical mastitis (Piccinini et al 2005;Zecconi et al 2018), but udder inflammation was observed even below 100,000 cells/mL (Zecconi et al 2006;Merle et al 2007;Piccinini et al 2007;Baumert et al 2009;Schwarz et al 2011), and nearly half of contagious pathogens have a SCC below 100,000 cells/ml (Zecconi et al 2003;Zecconi 2010).…”
Section: Introductionmentioning
confidence: 99%
“…SCC was also used to define udder health status. A value of SCC >200,000 cells/mL was used to define subclinical mastitis (Piccinini et al 2005), and by Italian Breeder Association nationwide to define subclinical mastitis in MTR.…”
Section: Data Collectionmentioning
confidence: 99%
“…The content of lysozyme in human milk ranges from 3 to 3000 µg/ml, and the typical concentration is about 200–400 µg/ml [16], [17]; however, only trace amounts are found in the breast milk of ruminants. Bovine milk typically contains only 0.05–0.22 µg/ml of lysozyme [16], [18]. In addition, its activity is 1/10 of lysozyme from human breast milk [16], [19].…”
Section: Introductionmentioning
confidence: 99%